Estimasi Cadangan Hidrokarbon Dengan Menggunakan Metode Monte Carlo dan Volumetrik Pada Lapisan LCB 3.2 Di Lapangan AP Kompleks, Formasi Cibulakan Bawah, Sub-Cekungan Jatibarang Pada Dalaman Cipunegara - Agustina Prihantini (Jurnal Migasian, 2022)
North West Java is one of the main oil areas in Indonesia. Geologically, the West Java region is located in the land part of the North West Java basin which is one of the back arc basins in western Indonesia. The Lower Cibulakan Formation of the Jatibarang Sub Basin has good potential as a reservoir rock because the source rock area is aware of the presence of structural traps found in higher areas around the sub basin. Estimation as an important thing that needs to be done in the prospect and planning of field development. The well is a study of exploitation wells with limited data available. Reserve estimates use the Monte Carlo and volumetric methods. The Monte Carlo method is a probabilistic approach that can reduce the uncertainty factor, while the calculation is repeated using the 1000 distribution. Volumetric method is used to compare the results of the estimates using the Monte Carlo method. The result of the estimation of both methods is that the reserve value with Monte Carlo is 198,385 BCF, while the reserve value for volumetric reserves is 197,25 BCF. Based on the estimation results using the Monte Carlo and volumetric methods, the LCB 3.2 layer in the Lower Cibulakan Formation is a prospect zone for exploitation drilling and the prospect to be developed into a productive field and feasible for further development.